Financial Liberalization and Volatility in Emerging Market Economies - Philippe Aghion; Philippe Bacchetta; Abhijit Banerjee (Swiss National Bank, Study Center Gerzensee, 1998)
The recent East Asian crisis has highlighted the relationship between financial development and output volatility. In this essay we develop a simple model of a small open economy producing a tradeable good using a non-tradeable input and where firms access to borrowings and investment depends on current cash flows. We then show, first that macroeconomic volatility only occurs at intermediate levels of financial development; second, that whilst full financial liberalization, including an unrestricted opening to foreign lending, can destabilize an emerging market economy, in contrast output volatility can be avoided if the same economy opens up to foreign direct investment only. We also draw several policy conclusions regarding the adequate responses to financial crises.
Keywords: 330; Kleine offene Volkswirtschaft; Finanzmarktregulierung; Wechselkurspolitik; Volatilität; Kreditwürdigkeit; Auslandsinvestition; Theorie; Schwellenländer